Determination of DPYD Enzyme Activity in Korean Population. Issue 2 (April 2015) - Shin, Joong-Gon; Kang, Tae Sun; Cheong, Hyun Sub; Shin, Hee Jung; Park, Hyun Joo; Na, Han Sung; Shin, Hyoung Doo; Chung, Myeon Woo
Abstract : Background: Dihydropyrimidine dehydrogenase (DPYD) is an enzyme that regulates the rate-limiting step in pyrimidine metabolism, especially catabolism of fluorouracil. This study was performed to analyze the association between DPYD genetic variants and DPYD enzyme activity in the Korean population. Methods: We screened the genetic variants and analyzed the enzyme activity in 73 healthy Korean subjects (69 men and 4 women; mean age, 22.6 years). Direct sequencing was conducted using the ABI 3730XL system, and enzyme activity was determined using high-performance liquid chromatography. Results: A total of 83 genetic variants were observed. Among the identified genetic variants, 32 were polymorphic including 3 core and 11 novel genetic variants. Association analysis between each genetic variant and enzyme activity in Korean subjects showed that 2 novel genetic variants, − 832 G>A and − 131 C>A, induced a significant difference in enzyme activity ( P < 0.05). Conclusions: To our knowledge, this is the first study that has examined the association between enzyme activity and DPYD genetic variants in the Korean population. In this study, we identified novel genetic variants that are associated with the enzyme activity. These findings will be valuable for further pharmacogenetic studies and especially useful for personalized medicine. Abstract : Supplemental Digital Content is Available in the Text.